(untitled) (Research, Society and Development, 2021)
Indigenous bees are important pollinators of native plants. In the Caatinga there are about 193 species of bees belonging to 79 genera, of which 18 are meliponis. The objective of this work was to verify if there is influence of cardinal and collateral points in the nesting of bees Melipona subnitida Ducke and Frieseomelitta sp. in plant hosts from Caatinga. The work was developed in Santana do Seridó, state of Rio Grande do Norte, at Fazenda Morada da Jandaíra (6° 44´ 16´´S and 36° 43´ 13´´W). The width and height measurements of the nests were made with the aid of a measuring tape. A digital compass application for smartphone (iPhone® Model A 1533) was used to read the positioning of the nesting holes in relation to cardinal and collateral points. Wind speed, humidity and temperature were measured by an Oregon Scientific® mini meteorological station, WMR928NX. Absolute frequency analyzes were performed using the R v software. 2.15 (R Development Core Team, 2005). A total of 136 bee nests were analyzed. It was observed that the bees M. subnitida Ducke and Frieseomelitta sp. nest more frequently in Commiphora leptophloeos and Poincianella pyramidalis. As for the magnetic nesting orientation, these bees have distinct habits: the M. subnitida Ducke bee demonstrates greater nesting preference in the Northwest (NW) direction, while the Frieseomelitta sp. bee has a broad nesting preference in any magnetic orientation, except between 270 and 315º angles.